1996
DOI: 10.1007/bf01875418
|View full text |Cite
|
Sign up to set email alerts
|

An attempt towards differentiating attentional deficits in traumatic brain injury

Abstract: Attentional deficits in patients suffering traumatic brain injury (TBI) can occur with minor to severe impact to the brain. Based on reviews of both the cognitive and neurobehavioral literature, the following three concepts of attention are addressed: (a) arousal/alertness, (b) selective attention, and (c) energetic aspects of attention, which include such components as effort, resource allocation, and speed of processing. Within each concept, definitions are proposed, the underlying brain mechanisms are ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 80 publications
0
15
0
2
Order By: Relevance
“…Cognitive impairments are among the most common neuropsychiatric sequelae of traumatic brain injury (TBI) at all levels of severity, and typically include impairments of arousal, attention, memory, and executive functioning [1][2][3][4]. Although each of these domains of cognitive function may be disrupted by direct injury to cortical, subcortical, or brain stem elements of the distributed cerebral networks that support them, injury to the axons connecting these elements or providing them with the neurochemical input required for their function also contributes to post-traumatic cognitive impairments [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairments are among the most common neuropsychiatric sequelae of traumatic brain injury (TBI) at all levels of severity, and typically include impairments of arousal, attention, memory, and executive functioning [1][2][3][4]. Although each of these domains of cognitive function may be disrupted by direct injury to cortical, subcortical, or brain stem elements of the distributed cerebral networks that support them, injury to the axons connecting these elements or providing them with the neurochemical input required for their function also contributes to post-traumatic cognitive impairments [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The other group was referred to as 'overprocessors' and was characterized by processing incoming information even when the stimulus required no response. Niemann et al [14] further interpreted these results and speculated that 'underprocessors' might be associated with symptoms of apathy, indifference and lack of motivation, possibly due to dorsolateral pre-frontal lesions and that 'overprocessors' may be related to disinhibition and impulsive behaviour associated with orbitofrontal lesions.…”
Section: Introductionmentioning
confidence: 92%
“…However, the consensus regarding appropriate evaluation and treatment of attention deficits is rather limited. Even though attention deficit is a very basic issue in patients suffering from blunt traumatic brain injury (TBI) with diffuse axonal injury (DAI) and without overt focal damage, it is quite difficult to evaluate this deficit [1,[5][6][7]. A number of studies have found deficits in focused [8], and sustained visual attention [9][10][11] following severe TBI.…”
Section: Introductionmentioning
confidence: 99%